Institutional Trading around Corporate News: Evidence from Textual Analysis - Huang, Alan Guoming; Tan, Hongping; Wermers, Russ (Review of Financial Studies, 2020)
Abstract We examine institutional trading surrounding corporate news by combining a comprehensive database of newswire releases on U.S. firms with a high-frequency database of institutional trades. To identify the ability of institutions to predict or quickly interpret news, we form “news clusters” of related news about a particular firm that occurs in rapid succession. We find that institutions chiefly trade on the tone of news directly after the earliest news release in a cluster, and such news-motivated trading predicts returns over the following weeks. Our results suggest that institutional investors contribute to price efficiency through the speedy interpretation of public information.